2017
DOI: 10.1097/gox.0000000000001404
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Aesthetic Results of 100 Patients Who Underwent Rhinoplasty—Rhinoplasty Outcome Evaluation

Abstract: Background:To assess the long-term aesthetic results of rhinoplasty and predict the final outcome.Methods:The sample was composed of 100 patients (34 men and 66 women) between 23 and 57 years old (mean, 34.8) operated on exclusively for aesthetic reasons. The time elapsed from the operation ranged from 3 to 13 years with a mean of 6.8 years. The study used Rhinoplasty Outcome Evaluation questionnaire, a simple, reliable, validated, and widely used inventory.Results:The vast majority of patients (93%) were sati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…The mean (SD) preoperative SCHNOS-C score of 59 (21), were observed to decrease at postoperative follow-up intervals <2 months (16 [20], P < .05); 2 to 5 months (16 [19], P < .05); 5 to 8 months (18 [16]…”
Section: Cosmetic Subgroupmentioning
confidence: 95%
See 2 more Smart Citations
“…The mean (SD) preoperative SCHNOS-C score of 59 (21), were observed to decrease at postoperative follow-up intervals <2 months (16 [20], P < .05); 2 to 5 months (16 [19], P < .05); 5 to 8 months (18 [16]…”
Section: Cosmetic Subgroupmentioning
confidence: 95%
“…The mean (standard deviation [SD]) preoperative NOSE, SCHNOS-O, and SCHNOS-C score of 69 (19) [9], P < .05).…”
Section: Functional Subgroupmentioning
confidence: 99%
See 1 more Smart Citation
“…Rhinoplasty is one of the most challenging facial aesthetic treatments and the main and realistic objectives are the establishment of a harmony between nose and face, improvement in the patient's appearance and providing a functional nasal airway. 1,2 To obtain the best aesthetically and functionally outcome, an accurate facial analysis, a detailed surgical plan, and a clear communication about the aesthetic objectives should be done before surgery. 1,3 The appropriate surgery should be chosen not only based on the anatomical part to be reshaped but also according to what the patient expects about his/her appearance.…”
mentioning
confidence: 99%
“…Kuran et al and others evaluated the long-term effects of tip sutures and tip cartilage grafts, and suggested that cartilage grafts should be considered as cases in which dimensional changes are a priority. If minor dimensional changes with more rotational alterations are planned, tip-suture techniques that provide sculpting the nasal tip with a long-lasting satisfactory aesthetic outcome should be preferred 6,[17][18][19] .…”
Section: Discussionmentioning
confidence: 99%